Tamoxifen reduces silicone implant capsule formation in a mouse model. Issue 10 (16th August 2022) - Blum, Kevin M.; Mirhaidari, Gabriel J. M.; Zbinden, Jacob C.; Breuer, Christopher K.; Barker, Jenny C.
Abstract: Capsular contracture as a result of the foreign body response (FBR) is a common issue after implant‐based breast reconstruction, affecting up to 20% of patients. New evidence suggests that tamoxifen may mitigate the FBR. C57BL/6 female mice were treated with daily tamoxifen or control injections and implanted with bilateral silicone implants in the submammary glandular plane. Implants were removed en bloc after 2 weeks and the implant capsules were evaluated histologically. Tamoxifen treatment decreased capsule thickness, decreased the number of αSMA+ cells (477 ± 156 cells/mm control vs 295 ± 121 cells/mm tamoxifen, p  = 0.005 unpaired t test), and decreased CD31+ cells (173.9 ± 96.1 cells/mm 2 control vs 106.3 ± 51.8 cells/mm 2 tamoxifen, p  = 0.043 unpaired t test). There were similar amounts of pro‐ and anti‐inflammatory macrophages (iNOS 336.1 ± 226.3 cells/mm control vs 290.6 ± 104.2 cells/mm tamoxifen, p  > 0.999 Mann–Whitney test and CD163 136.6 ± 76.4 cells/mm control vs 94.1 ± 45.9 cells/mm tamoxifen, p  = 0.108 unpaired t test). Tamoxifen treatment in the mouse silicone breast implant model decreased capsule formation through modulation of myofibroblasts, neovascularization, and collagen deposition. Tamoxifen may be useful for reducing or preventing capsule formation in clinical breast implantations.